2017
DOI: 10.7189/jogh.07.011102
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in Shenzhen, China: epidemiological investigation and health care challenges

Abstract: BackgroundUnderstanding epidemiological characteristics of diabetes in a specific population will potentially benefit prevention and control of diabetes and policy–making. This study aimed to investigate the prevalence and awareness of diabetes, as well as its pharmacological, non–pharmacological and primary care management in Shenzhen, China.MethodsA cross–sectional study was conducted. We employed multistage cluster random sampling methods to select the participants. Face–to–face interview surveys were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Among the variables of predisposing factors from the Andersen model, age was the only significant variable associated with diabetes diagnosis, in particular, old seniors aged ≥ 75 increased risk odds of undiagnosed diabetes. Although previous studies have shown that prevalence of diabetes [4,12,13] including undiagnosed diabetes [13,39,40] increased with age, the effect of age on health service utilization was ambiguous [41], what may hinder the elderly in accessing health service utilization and diagnosis is worth further exploring. Some evidence showed that gender, education level and marriage status were related to health service utilization [41], but not in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the variables of predisposing factors from the Andersen model, age was the only significant variable associated with diabetes diagnosis, in particular, old seniors aged ≥ 75 increased risk odds of undiagnosed diabetes. Although previous studies have shown that prevalence of diabetes [4,12,13] including undiagnosed diabetes [13,39,40] increased with age, the effect of age on health service utilization was ambiguous [41], what may hinder the elderly in accessing health service utilization and diagnosis is worth further exploring. Some evidence showed that gender, education level and marriage status were related to health service utilization [41], but not in this study.…”
Section: Discussionmentioning
confidence: 98%
“…In China, the prevalence of diabetes presented a noticeable rise as well [9][10][11]. The results from a national survey [4] indicated that diabetes had already reached epidemic proportions in the general adult population, in particular, the prevalence of undiagnosed diabetes and pre-diabetes were underestimated and would become a major threat to public health in the near future if no measure was taken [12]. Therefore, studies of undiagnosed diabetes are of importance to early diagnosis and the reduction in complications of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are an estimated 114 million people with diabetes in China ( 1 ). According to statistics in 2013, about a quarter of diabetes-related deaths worldwide occurred in China ( 2 ). China has experienced one of the largest increases in the prevalence of diabetes globally and the significant increase in the prevalence of diabetes is largely attributable to type 2 diabetes (T2D) ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…China has experienced a rapid increase in obesity rates in the past three decades, with more than one-fifth of school-age children being overweight or obese [ 14 ]. Shenzhen, a city in southern China, has experienced very rapid economic development since the middle of the 20th century and is now a national economic center, representing one of the most developed regions in China [ 15 ]. In Shenzhen, the prevalence of overweight and obesity among school-aged children (mean age 10.3 years) was estimated at 20.2% during 2016–2017 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%